2020
DOI: 10.3390/su12020607
|View full text |Cite
|
Sign up to set email alerts
|

Partial Acidulation of Rock Phosphate for Increased Productivity in Organic and Smallholder Farming

Abstract: There is a need to investigate and identify locally available organic substrates with acidifying potential, which can be used as an additive in rock phosphate (RP)-organic material composting mixtures. This paper reviews attempts to increase P availability in the context of smallholder, low-input and organic farming, and presents a case study from Central India that used a participatory approach to address P deficiency issues in cotton-based organic systems. Study was conducted from 2010 to 2014 through 61 on-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…The organic cotton farmers are suggested to use balanced nutrient management, including region-specific crop rotation, intercropping with pulses, the recycling of crop residues, and the use of compost and FYM. To complement the nutrient supply, other sources such as de-oiled castor (Ricinus communis) cake and powdered rock phosphate are also recommended [14]. Pest management primarily relies on preventive measures, such as selecting robust cotton varieties [15], maintaining a diverse crop rotation, and intercropping with maize and pigeon pea or okra (Abelmoschus esculentus) as trap crops.…”
Section: Study Regionmentioning
confidence: 99%
“…The organic cotton farmers are suggested to use balanced nutrient management, including region-specific crop rotation, intercropping with pulses, the recycling of crop residues, and the use of compost and FYM. To complement the nutrient supply, other sources such as de-oiled castor (Ricinus communis) cake and powdered rock phosphate are also recommended [14]. Pest management primarily relies on preventive measures, such as selecting robust cotton varieties [15], maintaining a diverse crop rotation, and intercropping with maize and pigeon pea or okra (Abelmoschus esculentus) as trap crops.…”
Section: Study Regionmentioning
confidence: 99%
“…PAPRs may offer an economic means [3] of enhancing the agronomic effectiveness of indigenous PR sources that may otherwise be unsuited for direct application.…”
Section: Comparison Of P Uptake By the Maize Among Soil Treatmentsmentioning
confidence: 99%
“…This deficiency is more severe in the high rainfall (800 -1200 mm) regions of the country (Region III) where predominant soils are the highly weathered Oxisols and Ultisols with high phosphorous fixing capacities [2]. Although judicious application of inorganic P fertilizers is recognized as the most effective method for alleviating P deficiencies, their high cost and inaccessibility limit their use to the majority of Zambia farmers, particularly the smallholder farms [3]. Application of farm yard manures and crop residues does add some limited quantities at farm level [4] [5] due to their low P content.…”
Section: Introductionmentioning
confidence: 99%
“…This points to the need to find better ways to manage PR to enhance P availability to plants and increase agricultural productivity. Several studies have identified different possible ways to increase P availability from PR: grinding it and combining with compost (Nishanth and Biswas 2008) or manure (Zafar et al 2017), solubilizing it in milk sludge also known as buttermilk (Cicek et al 2020), or making use of phosphate solubilizing microorganisms (bacteria and fungi) (Abbasi et al 2015;Panhwar et al 2013). Low molecular weight organic acids (such as oxalic, malic, citric, lactic, malonic, tartaric, and succinic) have also been used to solubilize P from PR (Jamal et al 2018;Klaic et al 2017;Wahba et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the P recovery efficiencies from the first two approaches are only between 18 and 29% (Zafar et al 2017). Farmers in SSA lack the knowledge and skills to use P-solubilizing bacteria (PSB) and fungi and lack access to PSB inoculants (Mukhongo et al 2016) and there is inadequate information on how to use milk sludge or organic acids to dissolve PR (Cicek et al 2020;Zapata and Zaharah 2002). Information on the use of natural acids from organic materials, suitable ratio of PR to organic material concentrations, and the optimum time for PR dissolution are limited (if available at all).…”
Section: Introductionmentioning
confidence: 99%